A novel hybrid system consisting of direct ammonia solid oxide fuel cell, gas turbine and dual-loop organic rankine cycle (DA-SOFC-GT-ORC): Multi-objective optimization and performance analysis - Weihua Cai; Hao Zhang; Xunjian Che; Zhongnong Zhang; Qian Li; Benan Cai; Kexin Liu (Case Studies in Thermal Engineering)
Ammonia is a hydrogen carrier that emits no carbon and benefits from a well-established infrastructure for production, storage, and transport, making it an increasingly favored clean fuel. This paper introduces the first exploration and analysis of a Direct Ammonia fueled Solid Oxide Fuel Cell and Gas Turbine system with a Dual-Loop Organic Rankine Cycle (DA-SOFC-GT-ORC). We performed a multi-objective optimization for this system, with emphasis on enhancing both efficiency and economic feasibility. Under optimized conditions, the system achieves an exergy efficiency of 60.45 %, which is 10.64 % higher than that of a methane-fueled system. We analyze factors affecting system performance, including fuel flow rate, air flow rate, and fuel utilization rate. The results demonstrate that elevated temperature and pressure at the SOFC inlet improve system performance. The maximum exergy destruction is observed in the SOFC, heat exchangers, and gas turbine. Adding more cells improves system performance but also increases overall costs, with the minimum production cost per electrical unit achieved at 45,000 cells. The economic efficiency is marginally affected by air flow rate, yet considerably by fuel flow rate. For minor fluctuations in power demand, it is recommended to adjust the air flow rate to maintain high economic efficiency.